2002
DOI: 10.2134/jeq2002.0759
|View full text |Cite
|
Sign up to set email alerts
|

Soil Temperature, Nitrogen Concentration, and Residence Time Affect Nitrogen Uptake Efficiency in Citrus

Abstract: We try to elucidate which environmental and soil factors control nitrogen uptake efficiency in citrus. Effects of residence time and nitrogen (N) concentration (three 500-mL applications of 7 mg N L(-1), representative of reclaimed water used for citrus irrigation in central Florida, or one 150-mL application of 70 mg N L(-1)) on nitrogen uptake efficiency (NUE) of young citrus seedlings were studied. Increasing residence times from 2 to 8 h increased NUE from 36 to 82% and from 17 to 34% for high and low appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 0 publications
4
40
0
Order By: Relevance
“…The fraction N which is derived from the fertilizer (Ndff) was calculated according to Hardarson (1990) A potential nitrogen leaching (PNL) index was introduced to quantify effects of N rates on N leaching and potential ground water contamination, with values defined as follows: PNL = 100 -NUE for NUE <100% (Scholberg et al, 2002).…”
Section: Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fraction N which is derived from the fertilizer (Ndff) was calculated according to Hardarson (1990) A potential nitrogen leaching (PNL) index was introduced to quantify effects of N rates on N leaching and potential ground water contamination, with values defined as follows: PNL = 100 -NUE for NUE <100% (Scholberg et al, 2002).…”
Section: Calculationsmentioning
confidence: 99%
“…The logarithm of NUE linearly correlated with N rate at each phenological period; the slope of regression lines was significantly higher at flowering, which indicates the scarce response in N uptake when increasing N supply at early stages, thus resulting in an abrupt decrease in NUE. Slopes of correlation lines decreased later on, being the smoothest slope obtained at fruit growth period, as a result of the enhanced fertilizer N uptake in summer months when root system of the citrus trees is highly effective in taking up the N applied (Davies & Albrigo, 1994;Kubota et al, 1976aKubota et al, , 1976bScholberg et al, 2002). These results corroborate previous findings on the higher NUE when fertilizer was supplied on June (61%; Kubota et al, 1976b) if compared to earlier application on March (25%; Kubota et al, 1976a).…”
Section: Fertilizer N Uptake Efficiency: Seasonal Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced fertigation systems combine drip irrigation and fertilizer application to deliver water and nutrients directly to the roots of crops, with the aim of synchronising the the root-zone, thus providing ideal conditions for rapid uptake of water and nutrients. Scholberg et al (2002) demonstrated that more frequent applications of a dilute N solution to citrus seedlings doubled nitrogen uptake efficiency compared with less frequent applications of a more concentrated nutrient solution. Delivery of N through fertigation reduces N losses in the soil-plant system by ammonia volatilisation and nitrate leaching (Alva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate water supply is, therefore, critical in maximizing crop production, nutrient use efficiency (NUE), and quality of most horticultural crops. Efficient water use may promote an increase in fertilizer retention in the effective root zone, maximizing crop production and minimizing the potential of groundwater degradation (e.g., nitrate-nitrogen (NO 3 --N) leaching) (Scholberg et al, 2002). A simple goal of the ideal irrigation scheduling would be to increase crop production with the least amount of water, therefore minimizing water loss by deep percolation, runoff or evaporation.…”
Section: Irrigation and Drainage Systems On Sandy Soilsmentioning
confidence: 99%